If $\displaystyle a,b,n \in \mathbb{N}^+, \quad n \ge 2$

Prove that $\displaystyle (k = \frac{a^n+b^n}{(ab)^{n-1}+1} \in \mathbb{N}) \Rightarrow \exists c \in \mathbb{N} \; (k = c^n)$

Printable View

- May 14th 2010, 02:48 PMelimDivisibility and perfect power
If $\displaystyle a,b,n \in \mathbb{N}^+, \quad n \ge 2$

Prove that $\displaystyle (k = \frac{a^n+b^n}{(ab)^{n-1}+1} \in \mathbb{N}) \Rightarrow \exists c \in \mathbb{N} \; (k = c^n)$ - May 17th 2010, 06:05 PMchiph588@
This a stupendous problem! (Clapping) May I ask where you got this from?

I would love to take a crack at this right now but I'm so busy at the moment, but what I can offer you is this. Hopefully things will clear up for me in the coming week and I'll have a go at it. - May 17th 2010, 07:39 PMBruno J.
I'm going to bed now, but I'll just remark that, in general, the denominator is much bigger than the numerator. There may in fact be very few cases to check!

- May 18th 2010, 05:36 PMelimThe basics
When a = b, one can easily see that a = b = k = 1 = $\displaystyle 1^n$

Assume that $\displaystyle 1 \le a < b$ and $\displaystyle k \in \mathbb{N}^+$ satisties $\displaystyle a^n - k = b^{n-1} (k a^{n-1} -b)$

Consider 3 cases:

(1) $\displaystyle k > a^n$ (2) $\displaystyle k < a^n$ and (3) $\displaystyle k = a^n$

Try to prove that (1) leads to contradiction (2) forces $\displaystyle k=1$ and (3) gives non-trivial (a,b,k)'s - May 18th 2010, 06:41 PMchiph588@
- May 18th 2010, 08:44 PMmathman88
- May 29th 2010, 04:46 PMchiph588@
- May 30th 2010, 02:53 PMelim
ref

**Proof**We have $\displaystyle a = b, \; k=\displaystyle{\frac{a^n+b^n}{(ab)^{n-1}+1}} \in \mathbb{N}^+ \Rightarrow a=b=k=1=1^n$

Now assume that $\displaystyle a<b,\;n>1,\; a^n-k=(ka^{n-1}-b)b^{n-1}$

(1) If $\displaystyle k > a^n$ then $\displaystyle k > k-a^n = b^{n-1} (b-ka^{n-1}) \ge b^{n-1}$

$\displaystyle \quad \;$ thus $\displaystyle b > ka^{n-1} \ge k > b^{n-1}$. It's impossible.

(2) If $\displaystyle k < a^n$, then $\displaystyle ka^{n-1}-b = \displaystyle{\frac{a^n-k}{b^{n-1}}} < a$, $\displaystyle ka^{n-1} < a+b$, $\displaystyle (k-1)a^{n-1} < a+b - a^{n-1} \le b$

$\displaystyle \quad$ If $\displaystyle k > 1$, then $\displaystyle a^{n-1} \le (k-1)a^{n-1} < b$, $\displaystyle a^n-k = (ka^{n-1}-b)b^{n-1} \ge b^{n-1} > (a^{n-1})^{n-1} \ge a^n$,

$\displaystyle \quad \;$ that's wrong and so $\displaystyle k=1=1^n$

(3) If $\displaystyle k = a^n$ then $\displaystyle b=ka^{n-1}=a^{2n-1} \; b^n = a^{2n^2-n} = a^{2n(n-1) + n}$ hence $\displaystyle \displaystyle{\frac{a^n+b^n}{(ab)^{n-1}+1}=\frac{a^n(1+a^{2n(n-1)})}{(a^{2n})^{n-1}+1}} = a^n$